Peran Islam: Mengarahkan Perkembangan IPTEKS untuk Akuntansi Syariah di Era Digital: The Role of Islam: Directing the Development of Science and Technology for Sharia Accounting in the Digital Era - Athifa Salsabila Malca; Amalina Nafi’ah Ramadhani; Ardia Pramesti Regita Cahyani; Nandadiya Reikhannun Yanuary; Adelia Mega Tsuroyyaa (Litera Academica Publishing, 2025)
The development of science and technology in the digital era has brought significant transformation to sharia accounting practices. This research analyzes Islam's role in directing science and technology development for sharia accounting in the digital era through qualitative literature study. Results show that digital technologies such as blockchain, AI, big data, and cloud computing enhance efficiency, transparency, and accountability in sharia accounting. Main challenges include limited competent human resources, different standards across countries, technology adaptation difficulties, and inadequate regulations. Islam plays a fundamental role through ijtihad concept encouraging innovation and ethical principles (honesty, justice, transparency, accountability) as the foundation for technology development. The research emphasizes stakeholder collaboration importance to develop technology-based sharia accounting systems aligned with Islamic values, recommending digital literacy improvement, standards harmonization, regulatory development, and technology-based education strengthening.